2010
DOI: 10.1002/dc.21592
|View full text |Cite
|
Sign up to set email alerts
|

Micronucleus and its applications

Abstract: Micronucleus (MN) is a small additional nucleus and is readily identifiable by light microscopy. Biologically, micronuclei are the chromosome fragments or whole chromosomes that lag behind at anaphase during nuclear division. MN occurs due to genetic damage of the cell and the MN scoring is the indicator of the genetic damage. Therefore MN scoring can be used in various clinical setting such as to supervise genotoxicity, biomonitoring of diseases, screening of preneoplastic diseases and identification of high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
116
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(124 citation statements)
references
References 54 publications
3
116
0
5
Order By: Relevance
“…34 The micronuclear test being the most sensitive and the most powerful statistical tool to evaluate DNA breaks, which indicate potential mutations. 35 Meanwhile, Results showed that three types of honey, which used in this study formed by different feed sources (HS, HW and HF, had no significant effect on the induction of micronuclei in bone marrow cells, which showed nearly the same values of control as shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…34 The micronuclear test being the most sensitive and the most powerful statistical tool to evaluate DNA breaks, which indicate potential mutations. 35 Meanwhile, Results showed that three types of honey, which used in this study formed by different feed sources (HS, HW and HF, had no significant effect on the induction of micronuclei in bone marrow cells, which showed nearly the same values of control as shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The comparison indicates that micronuclei formation in epithelial cells may be overestimated with Pap stain. 11 However, the Pap stain is still being used. The reasons to use Papanicolaou stain in this study were simple to use, less time consuming, and economical.…”
Section: Discussionmentioning
confidence: 99%
“…The MN test is a noninvasive, cost-effective, and easily acceptable procedure by patients. [10][11][12] Based on this background, this study was undertaken to identify the feasible and economical method that could be used as a screening test in high-risk population for identifying the effects of genomic instabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Conventionally prepared and May-Grünwald-Giemsa (MGG) stained slides were used for MN counting. For the evaluation of MN, we used the following preestablished criteria: a diameter smaller than 1/3 of the main nucleus, round/oval shape with regular contours, same staining intensity with the main nucleus, and no connection to the main nucleus (3,17) (Figure).…”
Section: Methodsmentioning
confidence: 99%